Translational applications of cardiovascular genomics: opportunities and challenges - Hingorani, Aroon (Henry Stewart Talks, 2008)
Ischaemic heart disease, Valvular heart disease, Heart muscle disease, Monogenic form of common disorder, Single gene disorders and cardiovascular disease, Mutation both necessary and sufficient to lead to disease, Genetic basis of the common form of CHD, Polygenic form of common disorder, Complex disorders, Study design, Candidate genes or whole genome, Genome-wide association studies, A new dawn for genetics of complex disorders and traits, Relationship between allele frequency and effect size, Genetic architecture of common disease, Translation of genomic discoveries, Potential advantages of genetic tests, Predictive genetic screening for CHD, Low penetrance polymorphisms, Multiple risk alleles, Why genetic testing might perform poorly as a discriminatory test, Genotype and prediction of CHD, Using genotype to gain insight into the causes of CHD, Unique properties of genotype, Novel biomarkers and CVD, CVD and the translational gap, Attrition of new molecular entities, Association of a quantitative trait with clinical events may have a non-causal explanation, Investigating causal role through experimentation, Validation of a drug target requires experimentation, Non-experimental studies in humans, The "cholesterol myth", Identification and validation of a "drug-target", The final arbiter of the validity of the therapeutic target is the RCT in humans, Nature's randomized trials, Homocysteine and stroke, Triangulation between genotype, biochemical risk marker and event rate, Mendelian randomization